Evolutionary Trends in the Landscape of Hausa Open Spaces: Key Enablers of Habe City Planning Mythology - Zhu Jie; Maimuna Saleh-Bala; Adamu Yakubu; Sadiq Abdullahi Nashe; Danjuma Abdu Yusuf (The Directorate for Research and Community Services, Institut Teknologi Bandung, 2023)
This study took the ‘origin-pattern-function’ of landscape progression as the central theoretical framework and conducted a systematic study on the evolution of open-space landscape patterns in Habe cities, situated between the river Niger and the river Benue in northern Nigeria. This study aimed to explore the embedded landscape cosmology in Hausaland and the origins of its historic mythology. A descriptive research and review approach was adopted, to explain and interpret prevailing practices, existing circumstances, attitudes, reasons, and on-going processes. It unveils the planning of open spaces and houses according to an ancient cosmology that organized towns during the Habe Hausa Dynasty. The open spaces appear to be a sphere of convergent and divergent forces that maintain a delicate balance, whereas the outcrop hills of central Hausaland are domicile places with religious appeal and better defensibility. Further, the physical effects of Islamic influence are visible in the landscape of Hausa cities, such as locating a mosque in the heart of the city as well spatial expressions of the practice of the seclusion of women. The study also revealed that the concept of triple outdoor space in the landscape of Habe cities is identical with that of the traditional Hausa family dwellings enclosed by a compound wall with a gate. This paper presents the key enablers of the Hausa cities’ transformation into commercial, administrative, religious, and agricultural centers. It recommends that in the event of landscape development without certain public guidelines or natural practices, complicated mediation measures should be invoked if disorder is not to prevail. It finally seeks a comprehensive application of local practices and innovative methods with the aim of averting vulnerability of urbanization.